2021
DOI: 10.1093/rheumatology/keab597
|View full text |Cite
|
Sign up to set email alerts
|

Long-term effects of early pulse methylprednisolone and intravenous immunoglobulin in patients with dermatomyositis and polymyositis

Abstract: Objective To evaluate the long-term effects of pulse intravenous methylprednisolone (IVMP) or intravenous immunoglobulin (IVIG) administered during the first year of diagnosis in dermatomyositis (DM) and polymyositis (PM) patients. Methods This is a retrospective single-center cohort study of patients with DM/PM followed for up to 4 years from 2001 to 2017. We used Cox regression models to estimate hazard ratios (HRs) and ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Previous studies have shown an increase in patient survival or higher rates of complete clinical response when glucocorticoids were administered earlier and at high doses [32,33]. In addition, an early approach to targeted treatment with IVMP and/or IVIg was associated with a potential reduction in long-term muscle disability and better outcomes (complete clinical response and discontinuation of corticosteroids) [34,35]. It is important to emphasize that adjuvant therapies with immunomodulators and immunosuppressants, such as leflunomide, seem to be safe and effective for cases of refractory DM with primary cutaneous activity [36].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown an increase in patient survival or higher rates of complete clinical response when glucocorticoids were administered earlier and at high doses [32,33]. In addition, an early approach to targeted treatment with IVMP and/or IVIg was associated with a potential reduction in long-term muscle disability and better outcomes (complete clinical response and discontinuation of corticosteroids) [34,35]. It is important to emphasize that adjuvant therapies with immunomodulators and immunosuppressants, such as leflunomide, seem to be safe and effective for cases of refractory DM with primary cutaneous activity [36].…”
Section: Discussionmentioning
confidence: 99%
“…This scheme can be repeated every 21-28 days until a significant improvement is achieved. Despite the limited evidence, it is possible to associate IVIg 2 g/kg divided over three to five days to reduce the risk of infections related to IVMP, achieve faster recovery, decrease the necessity of glucocorticoids, and avoid long-term sequelae of SAMs (52,53). Cyclophosphamide is one of the most studied medications in SAM-ILD, considered as an option in rapidly progressive forms with respiratory failure, although it is usually reserved for ILD refractory to other immunosuppressive drugs due to concerns of serious adverse effects, such as infections and bladder toxicity (26).…”
Section: Reviewmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic and the attendant risk of infection have been a serious cause for concern among patients with idiopathic inflammatory myopathies (IIMs) and other systemic autoimmune and inflammatory diseases (SAIDs) [ 1 ]. Patients with IIMs represent a unique vulnerable subgroup, as they typically require long-term treatment with multiple immunosuppressive and immunomodulatory (IS/IM) therapy [ 2 , 3 ], which is associated with impaired host response to infections [ 3 , 4 ]. Patients with IIMs may also have multiple sequelae of their disease (e.g., impaired strength, lung fibrosis) and frequent comorbidities (e.g., cardiovascular disease, obesity, and diabetes) [ 5 ].…”
Section: Introductionmentioning
confidence: 99%